Study on quaternary concrete micro-structure, strength, durability considering the influence of multi-factors. (15th May 2017) - Dave, Niragi; Misra, Anil Kumar; Srivastava, Amit; Sharma, Anil Kumar; Kaushik, Surendra Kumar
Highlights: Quaternary concrete micro-structures. Quaternary concrete strength and durability. Supplementary cementitious materials like silica flume, GGBS, Metakaolin, Fly ash. Rapid Chloride Permeability Test (RCPT) and sulfate attack. Development of new quaternary concrete. Abstract: Experimental study on the effect of mechanical behavior of quaternary binders, prepared using various supplementary cementitious materials was performed. Fly ash (FA), Ground Granulated Blast furnace Slag (GGBS), Metakaolin (MK) and Silica Fume (SF) were blended in pre-determines proportions by replacing 30–50% of Ordinary Portland Cement (OPC) by weight. The water/binder ratio and total cementitious materials for pre-decided M40 grade quaternary mix were kept constant for all mixes at 0.40 and 440 kg/m 3, respectively. Tests were carried out to characterize the mechanical behavior of quaternary blended concretes at 7, 28, 56, 90, 180 and 365 days and results obtained were compared with the corresponding values obtained for controlled concrete (100% OPC) as well as binary mixes (70% OPC:30% FA and 50% OPC: 50% FA). The entire specimen were prepared, cured and tested as per the Indian standard code of practice. In addition to that durability of the quaternary mix was determined via Rapid Chloride Permeability Test (RCPT) and sulfate attack test. The synergistic action of the cement with the addition of supplementary cementitious materials has a positive effect vis-a-vis the durability and in few combinations of mixes strength of the concrete with quaternary binders was found better than that of the controlled and binary mix concrete. Based on the test results, optimum mixes of FA, SF and GGBS/MK as partial replacement to the OPC as quaternary binder would be a better option compare to 100% controlled concrete.